Effectiveness of intermittent preventive treatment with sulfadoxine–pyrimethamine during pregnancy on placental malaria, maternal anaemia and birthweight in areas with high and low malaria transmission intensity in Tanzania. Issue 9 (26th June 2014) - Mosha, Dominic; Chilongola, Jaffu; Ndeserua, Rabi; Mwingira, Felista; Genton, Blaise
Abstract Objective To assess the effectiveness of IPTp in two areas with different malaria transmission intensities. Methods Prospective observational study recruiting pregnant women in two health facilities in areas with high and low malaria transmission intensities. A structured questionnaire was used for interview. Maternal clinic cards and medical logs were assessed to determine drug intake. Placental parasitaemia was screened using both light microscopy and real‐time quantitative PCR. Results Of 350 pregnant women were recruited and screened for placental parasitaemia, 175 from each area. Prevalence of placental parasitaemia was 16.6% (CI 11.4–22.9) in the high transmission area and 2.3% (CI 0.6–5.7) in the low transmission area. Being primigravida and residing in a high transmission area were significant risk factors for placental malaria (OR 2.4; CI 1.1–5.0; P = 0.025) and (OR 9.4; CI 3.2–27.7; P < 0.001), respectively. IPTp was associated with a lower risk of placental malaria (OR 0.3; CI 0.1–1.0; P = 0.044); the effect was more pronounced in the high transmission area (OR 0.2; CI 0.06–0.7; P = 0.015) than in the low transmission area (OR 0.4; CI 0.04–4.5; P = 0.478). IPTp use was not associated with reduced risk of maternal anaemia or low birthweight, regardless of transmission intensity. The number needed to treat (NNT) was four (CI 2–6) women in the high transmission area and 33 (20–50) in the low transmission area to prevent one case of placental malaria. Conclusion IPTp may have an effect on lowering the risk of placental malaria in areas of high transmission, but this effect did not translate into a benefit on risks of maternal anaemia or low birthweight. The NNT needs to be considered, and weighted against that of other protective measures, eventually targeting areas which are above a certain threshold of malaria transmission to maximise the benefit.